2015
DOI: 10.5536/kjps.2015.42.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycopene on the Expression of Lipid Metabolism, Glucose Transport and Pro-Inflammatory Related Genes in Chickens

Abstract: The present study aimed to investigate the effects of lycopene on hepatic metabolic-and immune-related gene expression in laying hens. A total of 48 25-week-old White Leghorn hens were randomly allocated into four groups consisting of four replicates of three birds: control (basal diet), T1 (basal diet + 10 mg/kg of tomato powder-containing lycopene), T2 (basal diet + 10 mg/kg of micelles of tomato powder-containing lycopene), and T3 (basal diet + 10 mg/kg of purified lycopene). Chickens were fed ad libitum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Also, this improvement may be due to the role of lycopene in enhancing digestive enzyme activities, which increase the efficiency of nutrients use, rapid growth and organs development, and body weight (Jang & Moon, 2015). Similarly, with the present results, Leke et al (2018) indicated that adding dry tomato powder to broiler diet by 12% led to an increase in carcass weight.…”
Section: Production Performancesupporting
confidence: 81%
“…Also, this improvement may be due to the role of lycopene in enhancing digestive enzyme activities, which increase the efficiency of nutrients use, rapid growth and organs development, and body weight (Jang & Moon, 2015). Similarly, with the present results, Leke et al (2018) indicated that adding dry tomato powder to broiler diet by 12% led to an increase in carcass weight.…”
Section: Production Performancesupporting
confidence: 81%